APOBEC3H polymorphisms and susceptibility to HIV-1 infection in an Indian population - Naruse, Taeko K; Sakurai, Daisuke; Ohtani, Hitoshi; Sharma, Gaurav; Sharma, Surendra K; Vajpayee, Madhu; Mehra, Narinder K; Kaur, Gurvinder; Kimura, Akinori (Journal of human genetics, 2016)
Human APOBEC3H (A3H) is a member of APOBEC cytidine deaminase family intensively constraining the HIV-1 replication. A3H is known to be polymorphic with different protein stability and anti-HIV-1 activity in vitro. We recently reported that A3H haplotypes composed of two functional polymorphisms, rs139292 (N15del) and rs139297 (G105R), were associated with the susceptibility to HIV-1 infection in Japanese. To confirm the association of A3H and HIV-1 infection in another ethnic group, a total of 241 HIV-1-infected Indian individuals and ethnic-matched 286 healthy controls were analyzed for the A3H polymorphisms. The frequency of 15del allele was high in the HIV-1-infected subjects as compared with the controls (0.477 vs 0.402, odds ratio (OR)=1.36, P=0.014). Haplotype analysis showed that the frequencies of 15del-105R was high (0.475 vs 0.400, OR=1.36, permutation P=0.037) in the HIV-1-infected subjects, confirming the association of A3H polymorphisms with the susceptibility to HIV-1 infection.